Fe‐O Clusters Anchored on Nodes of Metal–Organic Frameworks for Direct Methane Oxidation. Issue 11 (1st February 2021) - Zhao, Wenshi; Shi, Yanan; Jiang, Yuheng; Zhang, Xiaofei; Long, Chang; An, Pengfei; Zhu, Yanfei; Shao, Shengxian; Yan, Zhuang; Li, Guodong; Tang, Zhiyong
Abstract: Direct methane oxidation into value‐added organic oxygenates with high productivity under mild condition remains a great challenge. We show Fe‐O clusters on nodes of metal–organic frameworks (MOFs) with tunable electronic state for direct methane oxidation into C1 organic oxygenates at 50 °C. The Fe‐O clusters are grafted onto inorganic Zr6 nodes of UiO‐66, while the organic terephthalic acid (H2 BDC) ligands of UiO‐66 are partially substituted with monocarboxylic modulators of acetic acid (AA) or trifluoroacetic acid (TFA). Experiments and theoretical calculation disclose that the TFA group coordinated with Zr6 node of UiO‐66 enhances the oxidation state of adjacent Fe‐O cluster due to its electron‐withdrawing ability, promotes the activation of C−H bond of methane, and increases its selective conversion, thus leading to the extraordinarily high C1 oxygenate yield of 4799 μmol gcat −1 h −1 with 97.9 % selectivity, circa 8 times higher than those modulated with AA. Abstract : Fe‐O clusters are synthesized on nodes of UiO‐66 simultaneously coordinated with trifluoroacetic acid (TFA) or acetic acid (AA) for direct methane oxidation. The TFA group coordinated with Zr6 node of UiO‐66 enhances the oxidation state of adjacent Fe‐O cluster, promotes the activation of C−H bond of methane, and increases its selective conversion into C1 oxygenates.